Reshaping the African Union Mission in Somalia: From AMISOM to ATMIS - Mbiavanga Ajú, Miguel (The HORN Bulletin, 2022)
Authorised in March 2007, AMISOM’s mandate officially ended on March 31, 2022 giving way to a newly established African Union Transition Mission in Somalia (ATMIS) which came into effect on April 1, 2022. Confronted with a myriad of problems ranging from logistical challenges, geopolitical interests by state actors involved both at global and regional level to the country’s internal political wrangling and continued threat posed by al-Shabab, the African Union is once again reshaping its policy in Somalia. After fifteen years of mixed results, the regional body has remained resolute in its commitment and quest for peace and consolidation of state-building in Somalia. This time, there is a heightened sense of purpose with ambitious and clearly defined targets for its mission, tight deadlines, and a well-defined exit strategy. This article explores the challenges of the transition and responsibilities placed into the hands of a still weak Federal Government of Somalia (FGS). More specifically, the prospect for peace and security in the most conflict-ridden nation of the Horn of Africa with the related regional implications and beyond in a post AMISOM and ATMIS landscape are discussed. A critical assessment of AMISOM’s experience and the overly ambitious transition plan suggests that the emerging scenario could yet again fall short of expectations in the quest for stability and lasting peace will continue to remain an elusive grand ambition in Somalia.